Association of Maternal Prepregnancy BMI and Plasma Folate concentrations with Child Metabolic Health - Wang, Guoying (JAMA Pediatr, 2016)
IMPORTANCE: Previous reports have linked maternal prepregnancy obesity with low folate concentrations and child overweight or obesity (OWO) in separate studies. The role of maternal folate concentrations, alone or in combination with maternal OWO, in child metabolic health has not been examined in a prospective birth cohort. OBJECTIVE: We tested the hypotheses that maternal folate concentrations can significantly affect child metabolic health and that maternal sufficient folate concentrations can mitigate prepregnancy obesity-induced child metabolic risk. DESIGN: Prospective birth cohort study SETTING: The Boston Medical Center, MA, USA PARTICIPANTS: This study included 1517 mother-child dyads recruited at birth from 1998–2012 and followed prospectively up to 9 years (median age: 6.2 years, range: 2–9 years). MAIN OUTCOMES AND MEASURES: Child BMI z-score calculated according to U.S. reference data, OWO defined as BMI≥85(th) percentile for age and gender, and metabolic biomarkers (leptin, insulin, and adiponectin). RESULTS: An “L-shaped” relationship between maternal folate concentrations and child OWO was observed: the risk of OWO was higher in the lowest quartile (Q1) as compared to Q2–Q4 with an odds ratio (OR) of 1.45 (95% confidence interval [CI], 1.13 to 1.87). The highest risk of child OWO was found among children of obese mothers with low folate concentrations (OR, 3.05, 95%CI, 1.91 to 4.86) compared to children of normal weight mothers with folate concentrations in Q2–Q4 after accounting for multiple covariables. Among children of obese mothers, their risk of OWO was associated with 43% reduction (OR, 0.57, 95%CI, 0.34–0.95) if their mothers had folate concentrations in Q2–Q4 compared to Q1. Similar patterns were observed for child metabolic biomarkers. CONCLUSIONS AND RELEVANCE: In this urban low-income prospective birth cohort, we demonstrated an L-shaped relationship between maternal plasma folate concentrations and child OWO and the benefit of sufficient folate concentrations, especially among obese mothers. The “threshold” concentration identified in this study far exceeded the clinical definition of folate deficiency (<10.0 nmol/L), which was primarily based on the hematological effect of folate. Our findings underscore the need to establish “optimal” rather than minimal folate concentrations for preventing adverse metabolic outcomes in the offspring.